ARTISTIC EXPRESSION OF SPIRITUAL CRISIS: IMAGE AND IDEA IN THE STORY “THE DEATH OF THE USERER” - Mardanova Mohira Davron kizi (Western European Studies, 2025)
This article focuses on the artistic expression of spiritual decline and moral crisis in Sadriddin Ayni's work "The Death of the Usurer". Through the work, the author deeply reflects on the excessive pursuit of material benefits by man , the denial of spiritual values, and the resulting spiritual suffering. In the work, the image of Kori Ishkamba shows that usury is depicted not only as an economic, but also as a moral vice.Through such situations as spiritual decline, religious hypocrisy, superficial religiosity , and personal irresponsibility, the author warns society against immoral and spiritual pollution. This work, especially through its spiritual analysis, conveys to the reader the spiritual crisis of man and its tragic consequences in life. Ayni calls on society to spiritual awakening and emphasizes the need to restore spirituality. The article also examines literary and poetic approaches, image and sociopsychological contexts in the analysis of the work
Keywords: spiritual decline; usury; spirituality